APOE polymorphism distribution among Native Americans and related populations - Demarchi, Dario (2009)
Background: Apolipoprotein E (apoE, protein; APOE, gene) plays a central role in lipid metabolism. Three common alleles, E*2, E*3 and E*4 have quantitative effects on lipid and lipoproteins levels, which are major risk determinants of cardiovascular diseases in several populations. Given their clinical significance, it is of interest to know the distribution of APOE variants in populations from diverse ethnic groups, as well as to determine if this polymorphism presents variations that might be associated with given evolutionary factors. Aim: We report the distribution of APOE polymorphisms in Native American populations from South America, comparing it with other native populations of the Americas and Siberia. Subjects and methods: The sample consisted of 315 individuals from nine Native American populations living at subtropical latitudes of Argentina, Brazil and Paraguay. The extended analysis included 50 populations across South and North America, Greenland and Siberia. The geographic patterns of the variation were investigated through correlation analysis, spatial autocorrelation and analysis molecular of variance (AMOVA). Results: The incidence of the most common allele (APOE*3) in the sample analysed ranged from 0.78 to 0.98. The second allele in prevalence, APOE*4, varied from 0.00 to 0.17. The rare allele APOE*2 was found in five of the nine populations investigated. This variant was found in a male with both maternal and paternal Native American lineages, suggesting that this allele is present in Native Americans and hence should not be used as an indicator of admixture. APOE*3 and APOE*4 present, respectively, positive and negative associations with latitude, although the pattern is much more pronounced in the Northern Hemisphere than in South America. APOE*2 increases its frequency with latitude but this pattern is statistically significant only in South America. Conclusion: The overall APOE spatial pattern seems, in general, compatible with a directional demographic expansion which occurred in north-eastern Asia and much of the New World. The APOE*2 allele shows this pattern in South America but a random distribution in the Northern Hemisphere, suggesting that the possibility of selection should not be discarded.